2021
DOI: 10.3390/ejihpe11040104
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, Familiarity and Religious Beliefs about Vaccination among Health Science and Non-Health Science Students in a Malaysian Public University

Abstract: Vaccine hesitancy has surfaced globally within the last few decades, and the fears and misconceptions of people about vaccine safety and effectiveness have been identified as key factors for their under-utilization. The familiarity, attitudes, and religious beliefs of the public and of future healthcare practitioners regarding vaccination are extensive areas needing exploration. The present exploratory cross-sectional study was designed, planned and carried out on students enrolled in health science and non-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Similar to this, getting vaccinations were prevented in several prior non-COVID-19 instances in middle-income countries such as Malaysia in the cases of measles, mumps, and rubella (MMR). The religious rule against vaccines considered them to be “haram” (forbidden) due to the possible inclusion of ingredients originating from pigs [ 81 ]. A factor in Muslims’ growing hesitancy to get the COVID-19 vaccine may be the belief that vaccinations constitute a “medical assault” as well as concerns about the vaccines’ ingredients (such as whether they include pig gelatin) [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this, getting vaccinations were prevented in several prior non-COVID-19 instances in middle-income countries such as Malaysia in the cases of measles, mumps, and rubella (MMR). The religious rule against vaccines considered them to be “haram” (forbidden) due to the possible inclusion of ingredients originating from pigs [ 81 ]. A factor in Muslims’ growing hesitancy to get the COVID-19 vaccine may be the belief that vaccinations constitute a “medical assault” as well as concerns about the vaccines’ ingredients (such as whether they include pig gelatin) [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the role that vaccination plays in protecting individuals from infection and its dire consequences, and previous research has highlighted the significant role of perseverance as a protective factor against depressive symptoms among young adults who are at increased risk of COVID-19 infection ( Hou et al, 2021 ). In addition, recent research conducted among students of different disciplines showed that students had positive attitudes and beliefs and were familiar with vaccination despite a few knowledge gaps that can be enhanced further by introducing specialized immunization courses at the undergraduate level ( Elkalmi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunisation is a World Health Organization (WHO) recommended preventive measure in both children and adults that is usually achieved through the inoculation of an individual with weakened or killed microorganisms such as bacteria or viruses (Anderson et al 2015). The weakened 'pathogen stimulates the immune system into producing specific mediators that enable the host to generate an acquired immunity against the particular pathogen' (Elkalmi et al 2021(Elkalmi et al :1463. The effectiveness of a vaccination programme on a population centres on the number of people who received it (Elkalmi et al 2021).…”
Section: Religion and Vaccinationmentioning
confidence: 99%
“…The weakened 'pathogen stimulates the immune system into producing specific mediators that enable the host to generate an acquired immunity against the particular pathogen' (Elkalmi et al 2021(Elkalmi et al :1463. The effectiveness of a vaccination programme on a population centres on the number of people who received it (Elkalmi et al 2021). Vaccination, in the light of the given discussion, is a biomedical approach that is promoted by public health.…”
Section: Religion and Vaccinationmentioning
confidence: 99%